Pengaruh Kemampuan Kompetensi Pedagogik dan Kompetensi Profesional Pendidik terhadap Hasil Belajar Matematika Mahasiswa - Kusuma, Adi Candra; Dimas Rossiawan Hendra Putra; Hari Tri Wibowo (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This research aims to determine the influence of pedagogical competence and professional competence on student mathematics learning outcomes. This type of quantitative research with research subjects is Level 1 students in the odd semester of the 2024/2025 academic year with a sample of 239 students. Data collection techniques use observation, tests, interviews, and questionnaires. Data analysis was used by testing normality, hetroscedasticity, multicollinearity and autocorrelation using SPSS. The multiple linear regression equation obtained Y = 2,453 + 3,916 X1 + 5,053 X2. The independent variable consists of pedagogical competence (X1) and professional competence ability (X2) with the dependent variable, namely student mathematics learning outcomes (y). the independent variables (X1, An effective learning process must enable students to have meaningful experiences supported by educators who have pedagogical competence and professional competence.